A Criminological Review of Individuals Involved in Collective Crimes of Handling - Nasir, Muh; Aminah, Sitti (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
The crime of receiving money, especially when committed collectively, has a profound impact on the economic and social stability of society. This crime includes receiving, purchasing, or concealing the proceeds of a crime and often involves multiple individuals with various roles in the collective action. In the context of law enforcement, proving the involvement of individuals in the crime of receiving money is a significant challenge, so a coordinated strategy is necessary among the police, prosecutors, and courts to ensure that justice is upheld effectively.This study aims to examine the enforcement of criminal law against individuals involved in the crime of receiving stolen money and to analyse effective strategies for handling such cases. The research method employed is a normative legal approach, studying the application of criminal law norms in cases involving the receipt of money and the role of law enforcement agencies in the investigation and prosecution process.The results of the study indicate that law enforcement against the crime of receiving money requires solid and integrated coordination between law enforcement agencies. Strengthening the capacity of law enforcement officers, utilising information technology, and reforming legal policies are important steps in increasing the effectiveness of handling cases of money laundering. Additionally, increasing public legal awareness and protecting crime victims are integral components of this crime prevention strategy.Keywords: Handling, Law Enforcement, Crime.